Delay in effective therapy in anidulafungin-resistant Candida tropicalis fungaemia: Potential for rapid prediction of antifungal resistance with whole-genome-sequencing. (March 2019) - Chew, Ka Lip; Octavia, Sophie; Lin, Raymond Tzer Pin; Yan, Gabriel Zherong; Teo, Jeanette Woon Pei
Abstract: Objectives: This study investigated the feasibility of using whole-genome sequencing (WGS) for the prediction of antifungal resistance in anidulafungin-resistant Candida tropicalis candidaemia isolates. Methods: Next-generation sequencing was performed for three anidulafungin-resistant C. tropicalis isolates on an Illumina MiSeq system with in-house bioinformatics analysis. Results: Mutations in Fks1p associated with anidulafungin resistance were identified. Other mutations associated with varying levels of phenotypic resistance to fluconazole were also identified. Conclusions: These data demonstrate the potential to predict antifungal resistance using WGS. With improving technology, real-time WGS may be used for tailoring effective antifungal therapy in patients with candidaemia.